STRATEGI PENGEMBANGAN BISNIS BOLU KEMOJO DI BENGKALIS - Hafizah, Nurul; Syahnandra, Andre; Hendra, Joni (STAI Darul Qalam Tangerang, 2024)
This journal will discuss the strategy for developing the sponge kemojo business in Bengkalis. Micro, Small and Medium Enterprises (MSMEs) are businesses that continue to exist when corporate businesses are hit by a recession/monetary economic crisis. This proves that the MSME business is a business that has been tested and sturdy as one of the economic supports. In the city of Bengakalis, MSMEs are currently starting to develop in the food and cake sector, one of which is the sponge kemojo business in Bengkalis. Every business that is in a developing condition must have many competitors entering, for that it is necessary to have the right strategy so that the business can continue (sustainability). The purpose of this study is to explain the formulation of the sponge kemojo business development strategy in Bengkalis. The research method used in this journal is an explanatory qualitative approach. The unit of analysis in this study is the sponge kemojo business in Bengkalis, the data collection of this study is on the sponge kemojo business in Bengkalis. Based on the source, the data of this study consists of primary data and secondary data. Primary data consists of interviews with company owners, and employees of the sponge kemojo business in Bengkalis. Secondary data was obtained from the Central Statistics Agency. Secondary data consists of SME population data in Indonesia, and the total value of Indonesia's Gross Domestic Product (GDP). The data collection techniques in this study are interviews, observations, and documentation